Ainemukama, Fredinando (2022). Assessing the Impact of Covid-19 on Tourism Activities in Kisoro Region: A Case Study Of Kisoro Municipality. - Ainemukama, Fredinando (Kabale University, 2023)
The general objective of this study was assessing the impact of COVID-19 on tourism activities in Kisoro region. This study adopted the descriptive and exploratory research methodology. The target population consisted of 220 respondents, 110 respondents were selected as sample size. Questionnaires and interviews methods were used to collect data. The findings revealed that 80.0% of the respondents have had education on COVID-19, While 20.0% of the respondents stated that they have not received education on COVID-19. Basing on the above findings, it's evident that majority of the respondents have received education on COVID-19. majority of the respondents agreed that COVID-19 disorganized many tourism activities that led to closure of hotels and loss of human capital in the beginning of the pandemic in Kisoro Municipality. The study concludes that COVID 19 has led to increased poverty as many people lost their jobs. As travels were canceled and tourists reduced in numbers, tour companies were forced to stop some of their employees from working hence creating poverty.